Structure and physico-mechanical properties of hybrid compositions based on unsaturated polyester resin and portlandcement - D. A. Drozhzhin; L. B. Kandyrin; V. N. Kuleznev; N. B. Uriev (Тонкие химические технологии, 2006)
Strength and deformation properties of cured compositions based on unsaturated polyester resin and portlandcement were investigated in all range of concentrations. Optimal ratio of components which lead to high strength properties and high deformation ability was found